Applying Lucentis for the treatment of retinopathy of prematurity - S. V. Lesovoy; O. A. Boginskaya (Российский офтальмологический журнал)
Purpose: to evaluate the efficacy of Lucentis for the treatment of retinopathy of prematurity (ROP). Material and methods. 51 infants (102 eyes) with the gestational age between 24 and 33 weeks were given intravitreal injections of Lucentis, All patients selected had ROP stages I+, II+, III or III+ in zone 1, stage III+ in zone 2, or aggressive posterior ROP. The procedure was performed under general anesthesia; the dose, technique and the number of Lucentis injections conformed with the recommendations given in Lucentis instruction for use. If indicated, retinal laser photocoagulation was given after intravitreal injections using Supra (Quantel Medical, France) and Lachta-Mylon (Russia, Lasermedservis) laser equipment. Results. Clinical efficacy of intravitreal administration of Ranibizumab in infants with aggressive posterior ROP, zone 1 ROP, Stage III of zone 2 ROP was determined at 86.3 % (with no more than two injections). If ROP remains active after two injections, a change of therapy is recommended. Vascularization was noted to be complete in 51 % of cases. Conclusion. To achieve a maximum treatment effect of ROP with Lucentis, strict observation of indications criteria must take place.